The Intercellular Metabolic Interplay between Tumor and Immune Cells - Wang, Tingting; Liu, Guangwei; Wang, Ruoning (Frontiers in Immunology, 2014)
Functional and effective immune response requires a metabolic rewiring of immune cells to meet their energetic and anabolic demands. Beyond this, the availability of extracellular and intracellular metabolites may serve as metabolic signals interconnecting with cellular signaling events to influence cellular fate and immunological function. As such, tumor microenvironment represents a dramatic example of metabolic derangement, where the highly metabolic demanding tumor cells may compromise the function of some immune cells by competing nutrients (a form of intercellular competition), meanwhile may support the function of other immune cells by forming a metabolic symbiosis (a form of intercellular collaboration). It has been well known that tumor cells harness immune system through information exchanges that are largely attributed to soluble protein factors and intercellular junctions. Here, we will review recent advance on tumor metabolism and immune metabolism, provide examples of metabolic communications between tumor cells and immune system, which may represent a novel mechanism of conveying tumor-immune privilege in horizontal manner.